Genistein up-regulates tumor suppressor microRNA-574-3p in prostate cancer. - Takeshi Chiyomaru; Soichiro Yamamura; Shinichiro Fukuhara; Hideo Hidaka; Shahana Majid; Sharanjot Saini; Sumit Arora; Guoren Deng; Varahram Shahryari; Inik Chang; Yuichiro Tanaka; Z Laura Tabatabai; et al. (PLoS ONE, 2013)
Genistein has been shown to inhibit cancers both in vitro and in vivo, by altering the expression of several microRNAs (miRNAs). In this study, we focused on tumor suppressor miRNAs regulated by genistein and investigated their function in prostate cancer (PCa) and target pathways. Using miRNA microarray analysis and real-time RT-PCR we observed that miR-574-3p was significantly up-regulated in PCa cells treated with genistein compared with vehicle control. The expression of miR-574-3p was significantly lower in PCa cell lines and clinical PCa tissues compared with normal prostate cells (RWPE-1) and adjacent normal tissues. Low expression level of miR-574-3p was correlated with advanced tumor stage and higher Gleason score in PCa specimens. Re-expression of miR-574-3p in PCa cells significantly inhibited cell proliferation, migration and invasion in vitro and in vivo. miR-574-3p restoration induced apoptosis through reducing Bcl-xL and activating caspase-9 and caspase-3. Using GeneCodis software analysis, several pathways affected by miR-574-3p were identified, such as 'Pathways in cancer', 'Jak-STAT signaling pathway', and 'Wnt signaling pathway'. Luciferase reporter assays demonstrated that miR-574-3p directly binds to the 3' UTR of several target genes (such as RAC1, EGFR and EP300) that are components of 'Pathways in cancer'. Quantitative real-time PCR and Western analysis showed that the mRNA and protein expression levels of the three target genes in PCa cells were markedly down-regulated with miR-574-3p. Loss-of-function studies demonstrated that the three target genes significantly affect cell proliferation, migration and invasion in PCa cell lines. Our results show that genistein up-regulates tumor suppressor miR-574-3p expression targeting several cell signaling pathways. These findings enhance understanding of how genistein regulates with miRNA in PCa.